Perceptions regarding autism spectrum disorders among population of Kazakhstan - Laura Kozhageldiyeva; Lyazzat Kosherbayeva; Zhanara Sabyrdilda; Assem Kaukenova; Sandugash Kurmanalina (National Scientific Medical Center, 2024)
Introduction. The increase in the number of patients with autism spectrum disorders around the world leads to the need for public of its symptoms, for early detection and comprehensive care. The increase of public health literacy allows to improve and ease perception of population, families with ASD people. The purpose of the study is to understand the population's perceptions of ASD in Kazakhstan. Methods. A developed questionnaire in Kazakh and Russian languages was contributed among population of all regions of Kazakhstan during the first half of 2023. Survey provided using the online Google platform. 410 respondents attended the survey. Statistical analyses were performed using the SPSS13. Results. The questionnaire was developed using simulation situations, where the respondent chose the most suitable answer. It was found that the willingness to fully accept a child with ASD is not at a high level, regardless of residence (urban, rural). Fear and curiosity were noted as a high response among the population when simulating the situation of a child with ASD on the street. Despite a high level of willingness to help families, respondents identified gaps in knowledge or methods of helping children with ASD. It is known that children with ASD, depending on the severity of the condition, can study at school along with neurotypical children. There was a reluctance among the population to attend schools with neurotypical children, develop friendships, and even live in their neighborhoods. Conclusion. Changes in legislative acts, the development of Roadmaps for children with disabilities are only the tip of the iceberg in the formation of tolerance for people with disabilities. The creation of a host society should be a key factor in the organizations involved in shaping public opinion. Considering that this issue concerns all structures and areas, not only social programs, it is necessary to develop activities for various segments of the population on awareness and training in helping families with ASD.